The role of the matricellular protein SPARC in the dynamic interaction between the tumor and the host - Podhajcer, Osvaldo L.; Benedetti, Lorena Gabriela; Girotti, Maria Romina; Prada, Federico; Salvatierra, Edgardo; Llera, Andrea S. (Cancer and metastasis reviews, 2008)
Tumor growth is essentially the result of an evolving cross-talk between malignant and surrounding stromal cells (fibroblasts, endothelial cells and inflammatory cells). This heterogeneous mass of extracellular matrix and intermingled cells interact through cell–cell and cell–matrix contacts. Malignant cells also secrete soluble proteins that reach neighbor stromal cells, forcing them to provide the soil on which they will grow and metastasize. Different studies including expression array analysis identified the matricellular protein SPARC as a marker of poor prognosis in different cancer types. Further evidence demonstrated that high SPARC levels are often associated with the most aggressive and highly metastatic tumors. Here we describe the most recent evidence that links SPARC with human cancer progression, the controversy regarding its role in certain human cancers and the physiological processes in which SPARC is involved: epithelial–mesenchymal transition, immune surveillance and angiogenesis. Its relevance as a potential target in cancer therapy is also discussed.